Participatory Research Methods – Choice Points in the Research Process - Lisa M. Vaughn; Farrah Jacquez (Journal of Participatory Research Methods)
Participatory research (PR) encompasses research designs, methods, and frameworks that use systematic inquiry in direct collaboration with those affected by an issue being studied for the purpose of action or change. PR engages those who are not necessarily trained in research but belong to or represent the interests of the people who are the focus of the research. Researchers utilizing a PR approach often choose research methods and tools that can be conducted in a participatory, democratic manner that values genuine and meaningful participation in the research process. This article serves as an introduction to participatory research methods, including an overview of participatory research, terminology across disciplines, elements that make a research method participatory, and a model detailing the choice points that require decisions about which tools and methods will produce the desired level of participation at each stage of the research process. Intentional choices of participatory research methods, tools, and processes can help researchers to more meaningfully engage stakeholders and communities in research, which in turn has the potential to create relevant, meaningful research findings translated to action.